FEASIBILITY ANALYSIS OF SALT FARMERS BUSINESS IN WINI VILLAGE, INSANA UTARA DISTRICT, TIMOR TENGAH UTARA REGENCY - Emilia Khristina Kiha; Berno Benigno Mitang (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Indonesia is known as a maritime country with enormous potential for marine resources, both biological and non-biological. One of the wealth of non-biological marine resources owned by Indonesia is salt. As a maritime country with an area that is mostly ocean, Indonesia has a lot of economic potentials that comes from the wealth of the sea. Ironically, Indonesia is still a fairly large salt importer, especially in iodized salt and industrial salt. One of them is Wini Village is a salt-producing area in Kefamenanu City, which has an important role in the economy which is directed to increase income and production. This study aims to determine the income and feasibility of salt farmers in Wini Village, North Insana District. The research was carried out from July to August 2020. The research location is in Wini Village,North Insana District. Determination of the sample is done by using the sampling method (Random Sampling), as documentation of the implementation and the respondent's approach through observation, interviews, questionnaires where the number of samples used in the study was 68 respondents from the population in Wini Village as many as 70 salt farmers. The analysis used in this research is Income and Feasibility Analysis. The results of the analysis of the income obtained show that the average income of salt farmers in Wini Village is Rp. 6,912,300 tons/ha. The results of the feasibility analysis obtained show the Return Cost Ratio (R/C-ratio) value of 2.5 indicating R/C >1.